Exploring The Efficacy Of Black Soaps Derived From Palm Oil And Palm Kernel Oil With Caustic Potash (KOH) Extracted From Plantain Peel - Nnadikwe Johnson; Iheme Chigozie; Mbadike Columbus Asodike; Chinemerem Joy Johnson; Ibe Raymond Obinna (Jurnal Teknik Indonesia, 2025)
This study explores the potential of utilizing agricultural by-products, specifically plantain peels, as a source of caustic potash for producing high-quality black soaps from palm oil and palm kernel oil. The objectives were to evaluate the physicochemical properties and efficacy of these soaps in addressing various skin conditions. Plantain peels were sun-dried, burned, and processed to extract potassium hydroxide, which was then used in soap production. The results show that both soaps exhibited beneficial properties, with the palm kernel oil soap displaying a softer texture. The study highlights the potential of these black soaps in providing effective skincare solutions for common dermatological concerns, while also promoting sustainable utilization of agricultural by-products.